2023
DOI: 10.3389/fgene.2022.933636
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic application of exome sequencing in Chinese children with suspected inherited kidney diseases

Abstract: Background: Inherited kidney diseases (IKDs) are a group of kidney diseases characterized by abnormal kidney structure or function caused by genetic factors, but they are not easily diagnosed in childhood due to either nonspecific symptoms and signs or clinically silent symptoms in the early stages until the progressive stages, even end-stages. Early diagnosis of IKDs is very urgent for timely treatment and improving outcomes of patients. So far, the etiological diagnosis has been accelerated with the advance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…The observed genetic detection of 45% is a relative high yield compared with that previously reported for single-center or selected pediatric CKD cohorts. 1 , 15 , 16 However, this relatively high genetic diagnostic yield is comparable to other Israeli nationwide exome sequencing studies performed in children with neurodevelopmental disorders. 17 Moreover, we found high percentages of monogenic cases in children even when there was no positive family history, consanguinity, or syndromic features (26%, 29%, and 32% respectively).…”
Section: Discussionsupporting
confidence: 59%
“…The observed genetic detection of 45% is a relative high yield compared with that previously reported for single-center or selected pediatric CKD cohorts. 1 , 15 , 16 However, this relatively high genetic diagnostic yield is comparable to other Israeli nationwide exome sequencing studies performed in children with neurodevelopmental disorders. 17 Moreover, we found high percentages of monogenic cases in children even when there was no positive family history, consanguinity, or syndromic features (26%, 29%, and 32% respectively).…”
Section: Discussionsupporting
confidence: 59%
“…The corresponding diagnostic yield for non-specific CKD clinical presentations range from 32 to 52% for pediatric cases [45][46][47][48], 30 to 51% for pediatric/adult [49][50][51][52] and 9.3 to 34% for adult cases [53,54,63].…”
Section: Whole-exome Sequencingmentioning
confidence: 99%
“…In Rao et al the diagnostic yield was 29.1% for glomelular diseases, 61.4% for cystic renal disease 17% for CAKUT, 62.3% for renal tubular disease/renal calcinosis and 23.9% for CKD[11]. The mutated genes in Gao et al study were COL4A3, COL4A4, COL4A5, CLCN5, NPHS1, PKD1, PKHD1, SMARCAL1, OCRL and others[12]. In a study by Vaisitti et al, the yield was 20.6% for CAKUT, 74.4% for ciliopathies, 24.2% for glomerulopathies, 45.5% for nephrolithiasis, 45% for tubulopathies, and 7.1% for others[1].…”
mentioning
confidence: 94%
“…Bekheirnia et al stated quite a closer total diagnostic yield of 51% with 26% cases of cystic kidney disease, 21% of congenital anomalies of the kidneys and urinary tracts (CAKUT), 20% of hematuria, and 11% of proteinuria[10].Rao et al reported 55.3% of cases of glomerular disease; CAKUT accounted for 15.9% of cases; 8.3% of cystic renal disease; 15.9% of renal tubular disease and renal calcinosis or nephrolithiasis; and 4.6% of CKD 3-5 stages, while the total diagnostic yield was 42.10%[11]. Gao et al described that 41.8% of cases accounted for X-linked inherited kidney disease, while for both autosomal dominant and autosomal recessive inherited kidney disease, there were 29.1% of cases each, and the total diagnostic yield was 36.3%[12].Vaisitti et al reported that glomerular diseases accounted for 32.5%, ciliopathies for 20.4%, CAKUT for 17.8%, nephrolithiasis for 11.5%, tubular disease for 10.5%, and 7.3% for other diseases, and the total diagnostic yield was 37.1%[1]. Braun et al demonstrated 86.01% cases of nephrolithiasis and 13.99% cases of nephrocalcinosis, while the total diagnostic yield was 16.8%[13].…”
mentioning
confidence: 99%